Elevation of spectral components of electrodermal activity precedes central nervous system oxygen toxicity symptoms in divers - Posada–Quintero, Hugo F.; Derrick, Bruce J.; Ellis, M. Claire; Natoli, Michael J.; Winstead-Derlega, Christopher; Gonzalez, Sara I.; Allen, Christopher M.; Makowski, Matthew S.; Keuski, Brian M.; Moon, Richard E.; Freiberger, John J.; Chon, Ki H. (Communications medicine, 2024)
Background Oxygen-rich breathing mixtures up to 100% are used in some underwater diving operations for several reasons. Breathing elevated oxygen partial pressures (PO 2 ) increases the risk of developing central nervous system oxygen toxicity (CNS-OT) which could impair performance or result in a seizure and subsequent drowning. We aimed to study the dynamics of the electrodermal activity (EDA) and heart rate (HR) while breathing elevated PO 2 in the hyperbaric environment (HBO 2 ) as a possible means to predict impending CNS-OT. Methods EDA is recorded during 50 subject exposures (26 subjects) to evaluate CNS-OT in immersed (head out of water) exercising divers in a hyperbaric chamber breathing 100% O 2 at 35 feet of seawater (FSW), (PO 2 = 2.06 ATA) for up to 120 min. Results 32 subject exposures exhibit symptoms “definitely” or “probably” due to CNS-OT before the end of the exposure, whereas 18 do not. We obtain traditional and time-varying spectral indices (TVSymp) of EDA to determine its utility as predictive physio markers. Variations in EDA and heart rate (HR) for the last 5 min of the experiment are compared to baseline values prior to breathing O 2 . In the subset of experiments where “definite” CNS-OT symptoms developed, we find a significant elevation in the mean ± standard deviation TVSymp value 57 ± 79 s and median of 10 s, prior to symptoms. Conclusions In this retrospective analysis, TVSymp may have predictive value for CNS-OT with high sensitivity (1.0) but lower specificity (0.48). Additional work is being undertaken to improve the detection algorithm. Plain Language Summary This study looked at the effects of breathing high levels of oxygen during underwater diving and the risk of central nervous system oxygen toxicity. This toxicity can cause problems with movement, seizures or even drowning. We wanted to see if changes in skin and heart activity could help predict the symptoms of toxicity. We tested 26 divers (50 dives) in a special chamber. They breathed pure oxygen at increased pressure (equivalent to being underwater at 35 feet). 32 dives showed signs of toxicity, while 18 did not. We looked at the electrodermal activity (a measurement of the skin conductance) and heart rate data to see if they could warn of an issue. We found that in dives where toxicity symptoms definitely developed, there were significant changes in electrodermal activity around 57 s before symptoms appeared. While this method was very sensitive, it wasn’t always specific. We are working on improving this prediction method. This may be used to warn divers of dangerous gases so they can switch breathing gases or move to a shallower depth, and can improve the chances of escaping a disabled submarine. Posada-Quintero et al. study the dynamics of the electrodermal activity and heart rate while breathing at elevated oxygen partial pressures in a hyperbaric environment. Electrodermal activitycan be used to predict the onset of central nervous system oxygen toxicity symptoms in divers resulting from prolonged exposure to a hyperbaric environment.